Analysis of profitability, leverage, liquidity, and activity of financial distress basic study of chemical sub sector industry listed on BEI - Susanti, Metta; Samara, Aldi (LLDIKTI Wilayah 1 Sumatera Utara, 2021)
This study aimed to examine the effect of profitability, leverage, liquidity, and Activities Against Empirical Study of Financial Distress Basic Chemical Industry Sub-Sectors that registered in Indonesia Stock Exchange either simultaneously or partially. In this study for the Profitability variable using indicators: the ratio of Return On Assets (ROA), and Return On Equity (ROE) , for the Leverage variable using indicators: the ratio of Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) , to Liquidity variables using indicators: The ratio of cash (Cash Ratio), and the ratio of fast ( Quick Ratio ) , for variable activity using indicators: Inventory Turn Over ( ITO ), and Total Asset Turn Over ( TATO ) , to the variable Financial Distress use indicators: Financial Long Ratio (FLR) , Z-Score . . The population in this research is the basic chemical sub-sector industry listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period as many as 14 companies and the sample in this study is 12 . Hypothesis testing in this research was carried out using the Smart PLS (Partial Least Square) program. PLS is an alternative method of analysis with Structural Equation Modeling (SEM) based on variance. Outer Model Testing. Outer Model testing is done through Convergent validity, Discriminant Validity, Average Variance Extracted (AVE), Reliability Test. Inner Model Testing (Structural Model Evaluation). Inner model testing is done through the analysis of R Square (R2), Multicollinearity, F-Square (F2), Q-Square (Q2) and Analysis of Large Effects. The results of hypothesis testing in this study indicate that Profitability, Liquidity, Leverage and Activity can affect Financial Distress by 94.50% both simultaneously with the most dominant influence on Financial Distress partially derived from Profitability.